Investigating Indonesian EFL Teachers’ Perceptions on Blended Learning Strategy Amid Post-Covid-19 Era - Kristian Wijaya (SAGA: Journal of English Language Teaching and Applied Linguistics, 2022)
One of the good news of the new normal era is all humankind’s sectors are opened gradually by following the restricted health protocols. Without an exception, the educational sector is also allowed by the government to open schools in the green zone. As a result, a blended learning strategy is inevitably essential to support this post-covid-19 era. Blended learning strategy is a novel pedagogical approach where the online and offline systems are combined to promote more purposeful, organized, and meaningful learning dynamics for learners. This current small-scale qualitative study aimed to investigate the specific benefits of a blended learning strategy based on Indonesian EFL teachers’ perceptions. Thus, 5 open-ended written narrative inquiry questions were sent to two randomly invited Indonesian EFL teachers working in different elementary school institutions. The obtained research results unveiled that the effective utilization of blended learning strategy had successfully promoted more meaningful language learning enterprises, elevated EFL learners’ learning motivation, and increased their proactive learning behaviors. However, it should also be pondered carefully that the more contextualized language learning approaches, as well as stable internet connection, are urgently needed to strengthen the effectiveness of this learning approach. Due to the obtained research results, it is reasonable to be expected that Indonesian EFL experts, teachers, practitioners, and policy-makers can establish more collaborative networking to better design more qualified and meaningful blended learning activities in the future.